Islam and citizenship in Indonesia democracy and the quest for an inclusive public ethics - Hefner, Robert W. 1952- (Routledge, 2024)
"Islam and Citizenship in Indonesia examines the conditions facilitating democracy, women's rights, and inclusive citizenship in Indonesia, the most populous Muslim majority country and the third largest democracy in the world . The book shows that Muslim understandings of Islamic traditions and ethics have co-evolved with the understanding and practice of democracy and citizen belonging. Following 32 years of authoritarian rule, in 1998 this sprawling Southeast Asian country returned to electoral democracy. The achievement brought with it, however, an upsurge in both the numbers and assertiveness of Islamist militias, as well as a sharp increase in violence against religious minorities. The resulting mobilizations have pitted the Muslim supporters of an Indonesian variety of inclusive citizenship against populist proponents of Islamist majoritarianism. Seen from this historical example, the book demonstrates that Muslim actors come to know and practice Islam in a manner, not determined in an unchanging way by scriptural commands, but in co-evolution with broader currents in politics, society, and citizen belonging. By exploring these questions in both an Indonesian and comparative context, this book offers important lessons on the challenge of democracy and inclusive citizenship in the Muslim-majority world. Well written and informative, this book will be suitable for adoption in university courses on Islam, Southeast Asian Politics, Indonesian and Asian Studies, as well as courses dealing with religion, democracy, and citizen belonging in multicultural societies around the world. The book will be of interest to the general reader with an interest in Islam, citizenship, and democracy."
Includes bibliographical references and index
Keywords: Frau; Islam; Recht; Bürgerbeteiligung; Demokratie; Indonesien; Islam and politics / Indonesia; Islam and state / Indonesia; Citizenship / Religious aspects / Islam; Democracy / Religious aspects / Islam; Islamic fundamentalism / Indonesia; Indonesia / Politics and government / 1998-